METODE BERMAIN PERAN SEBAGAI STRATEGI UNTUK MENINGKATKAN KETERAMPILAN BERBICARA SISWA KELAS V SDN BOJONG RAWALUMBU VII - Arrohim, Dadan Nanda; Rikmasari, Rima; Budianti, Yudi (Universitas Islam 45 Bekasi, 2024)
This research is motivated by the lack of maximum speaking skills among students, this influences several factors such as: (1) intonation that is not well controlled, (2) due to lack of self-confidence, when forced to move forward, students' speaking skills will be limited. broken/disjointed, (3) students' pronunciation is not appropriate, and (4) the use of pronunciation words is not yet used. The aim of the research is to improve speaking skills through the Role Playing method. This research uses the Classroom Action Research (PTK) method with 3 (three) cycles. Each cycle carries out four stages, namely the planning, implementation, action and reflection stages. The number of students in the research class was 31 students. The number of male students was 17 and the number of female students was 14. Data collection techniques in this research used oral tests and observation. The indicator of success measured in this research is students' ability in reading comprehension skills. This researcher is declared successful if 80% of the total number of students achieve a score ≥ 75. The results show that class V classical completeness increased from cycle 1 with a classical completeness percentage of 55%, then in cycle II with a classical completeness percentage of 64% and cycle III reached the target classical completeness percentage of 84%. By using the Role Playing Method, teachers become more creative in using methods in learning and students become more interested in speaking to other students so that students' speaking skills can be completed. and thus it can be concluded that the Role Playing method can improve speaking skills in class V at SDN Bojong Rawalumbu VII.